Transition Metal Catalyzed Asymmetric Aryl Carbon–Heteroatom Bond Coupling Reactions - Zhou, Fengtao; Liu, Jianguang; Cai, Qian (Synlett, 2016)
Transition metal catalyzed coupling reactions of aryl halides with nucleophiles are valuable methods for the formation of aryl carbon–carbon or aryl carbon–heteroatom bonds. However, little attention has been focused on the asymmetric versions of such couplings. Besides direct coupling for the formation of axial chirality, asymmetric desymmetrization and kinetic resolution are two important strategies for achieving enantioselectivity in transition metal catalyzed aryl carbon–heteroatom couplings. This account summarizes recent progress made in our group on copper- or palladium-catalyzed asymmetric aryl carbon–nitrogen/oxygen coupling reactions using asymmetric desymmetrization or kinetic resolution strategies.1 Introduction2 Copper-Catalyzed Asymmetric N-Arylation2.1 N-Arylation via Asymmetric Desymmetrization2.1.1 First Type of Desymmetric N-Arylation2.1.2 Second Type of Desymmetric N-Arylation2.1.3 Double N-Arylation for Spirobilactams2.2 N-Arylation via Kinetic Resolution3 Asymmetric O-Arylation3.1 Palladium/Spirocyclic Diphosphine Ligand System for O-Arylation via Asymmetric Desymmetrization3.2 Palladium/Spirocyclic Diphosphine Monoxide Ligand System for O-Arylation via Asymmetric Desymmetrization3.3 Copper/Diamine System for O-Arylation via Asymmetric Desymmetrization4 Summary and Outlook
Keywords: carbon–heteroatom bonds; coupling; spiro compounds; asymmetric desymmetrization; kinetic resolution